Dual-Sensitive Gold-Nanocubes Platform with Synergistic Immunotherapy for Inducing Immune Cycle Using NIR-Mediated PTT/NO/IDO - Hsin-Yi Tsao; Hung-Wei Cheng; Chia-Chi Kuo; San-Yuan Chen (Pharmaceuticals, 2022)
Currently, the combination therapies based on immunotherapy have been rapidly developed, but the response rate has not always increased as expected. Nano-platform has become a potential strategy which can trigger multi-functions to increase immunotherapeutic efficacy via activating T-cells and photothermal effect. Herein, to avoid the self-degradation and provide pH-sensitive property, S-nitrosoglutathione (GSNO) was loaded in gold nanocubes (AuNCs) with polyacrylic acid (PAA) coating. Subsequently, the layer-by-layer (LbL) assembly of iron oxide nanoparticles (Fe3O4) and betanin can provide the conjugation of 1-methyl-D-tryptophan (1-M-DT) on the nanoparticle to form an NO gas-photothermal-immune nano-platform (GAPFBD) for achieving combinatory therapy of NO gas, photothermal therapy (PTT), and indoleamine 2,3-dioxygenase (IDO) immunotherapy. After irradiation by 808-nm laser, the GSNO was released under a lower pH environment due to the structural transformation of PAA and then transformed into NO production of 64.5 ± 1.6% under PTT. The combination of PTT and NO gas therapy can effectively eliminate cancer cells, resulting in a large amount of tumor-associated antigens (TAAs) compared to the individual treatment in vitro. Additionally, the released 1-M-DT inhibited IDO and combined with TAAs to enhance maturation of dendritic cells (DCs), indicating the excellent synergistic effect of PTT and NO with IDO inhibitors. These results revealed that this dual-sensitive nanoparticle presented a combination strategy of PTT/NO/IDO for the synergistic effect to promote DC maturation.